On debt service and renegotiation when debt-holders are more strategic - Bourgeon, Jean-Marc; Dionne, Georges (Journal of Financial Intermediation, 2013)
The contingent claims analysis of firm financing often presents a debt renegotiation game with a passive bank that does not use its ability to force liquidation strategically, contrary to what is observed in practice. We consider two motives that may lead a bank to refuse to renegotiate: maintaining its reputation to preserve its future lending activity and deterring firms from overstating their debt service abatement when they renegotiate. We show that with public information and private debt only, the optimal probability of debt renegotiation is high when the firm’s anticipated liquidation value is high. Under asymmetric information about liquidation value, the high liquidation value firm may be tempted to mimic the low liquidation value firm to reduce its debt service. To deter such mimicking, banks may sometimes refuse to renegotiate with firms having a low liquidation value.